2008
DOI: 10.1007/s12199-007-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunological alterations found in mesothelioma patients and supporting experimental evidence

Abstract: It is common knowledge that exposure to asbestos causes asbestos-related diseases, such as asbestosis, lung cancer and malignant mesothelioma, not only in people who have had long-term contact with asbestos in their work environment but also in residents living near factories that handle asbestos. Since the summer of 2005, these revelations turned into a large medical problem and caused and social unrest. We have focused on the immunological effects of both asbestos and silica on the human immune system. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Consistently, CD4 + T lymphocytes from MM patients exhibited significant upregulation of bcl-2 expression; similar results could be obtained for iNKT cells, a population with a high frequency of CD4 + T lymphocytes. 6 In conclusion, this study demonstrates, for the first time, a significant increase in the frequency of circulating iNKT cells in overexpressed in MPM patients, suggesting that long-term and low dose exposure to asbestos can lead to iNKT cell resistance to apoptosis. 6 In particular, it has been observed that asbestos fibers induce a cascade of intracellular events, such as the activation of Src family kinases, the enhancement of IL-10 transcription and secretion, the auto/paracrine activation of IL-10 receptors, and the IL-10-induced signal transducers and activators of transcription expressions of IFNγ and IL-4) at 37°C and 5% CO 2 in the presence of 10 μg/ml brefeldin A (Sigma-Aldrich), a transport inhibitor that prevents cytokine release from cells.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Consistently, CD4 + T lymphocytes from MM patients exhibited significant upregulation of bcl-2 expression; similar results could be obtained for iNKT cells, a population with a high frequency of CD4 + T lymphocytes. 6 In conclusion, this study demonstrates, for the first time, a significant increase in the frequency of circulating iNKT cells in overexpressed in MPM patients, suggesting that long-term and low dose exposure to asbestos can lead to iNKT cell resistance to apoptosis. 6 In particular, it has been observed that asbestos fibers induce a cascade of intracellular events, such as the activation of Src family kinases, the enhancement of IL-10 transcription and secretion, the auto/paracrine activation of IL-10 receptors, and the IL-10-induced signal transducers and activators of transcription expressions of IFNγ and IL-4) at 37°C and 5% CO 2 in the presence of 10 μg/ml brefeldin A (Sigma-Aldrich), a transport inhibitor that prevents cytokine release from cells.…”
Section: Discussionsupporting
confidence: 50%
“…diseases, such as MPM, even if the specific relationships between immune system and cancer are still unknown. 6,7 Starting from the early studies of Leigh and Webster,8 who demonstrated a close relationship between the presence of a lymphocyte infiltration into the tumor and a better prognosis, many evidences exist concerning pathological functional roles of different T-cell populations [e.g., cytotoxic T lymphocytes (CTL), helper T lymphocytes (Th), T suppressor (Ts) cells, natural killers (NK) cells] in MPM. 9 The existence of an imbalance in the T-cell subsets, with a significant reduction in Th to Ts ratios, as well as the possibility that MPM patients can spontaneously mount a tumor-specific immune response, have been reported in references 10-13.…”
Section: Introductionmentioning
confidence: 99%
“…This mini-review was part of ''Report of the 13th annual meeting of the Japanese Society of Immunotoxicology (JSIT 2006)'', and a brief summary of our investigations regarding the immunological effects of silica and asbestos was presented [1,2]. The other review was presented as ''Immunological alterations found in mesothelioma patients and supporting experimental evidence'', published online in February and on paper in March, 2008 [3,4]. In this mini-review, we presented immunological alterations found in patients with malignant mesothelioma (MM) and described the experimental background in which data were obtained from clinical samples [3,4].…”
Section: This Special Issue Of Environmental Health and Preventivementioning
confidence: 99%
“…The other review was presented as ''Immunological alterations found in mesothelioma patients and supporting experimental evidence'', published online in February and on paper in March, 2008 [3,4]. In this mini-review, we presented immunological alterations found in patients with malignant mesothelioma (MM) and described the experimental background in which data were obtained from clinical samples [3,4].…”
Section: This Special Issue Of Environmental Health and Preventivementioning
confidence: 99%
“…However, the roles and alterations of Th17 in silica-exposed patients are unknown and should be clarified through further research in order to obtain a better understanding of the immunological effects of silica on the human immune system. Many issues remain to be resolved, such as delineating the complications of SSc in SILs (Barnadas, 1986;Cowie, 1987Haustein, 1990Haustein & Anderegg, 1998;Sluis-Cremer, 1985), or those complications associated with malignant tumors such as mesothelioma and lung cancer in patients exposed to the mineral silicate asbestos (Greillier, 2008;Toyokuni, 2009;Miura, 2008). Regarding the relationship between tumor immunity and Treg function, it may be that Treg enhances cell numbers or function to reduce tumor immunity (Chattopadhyay, 2005;Danese & Rutella, 2007;Kretschmer, 2006).…”
Section: Silica-induced Dysfunction Of the Treg Fraction In Silsmentioning
confidence: 99%